Analisis Perilaku Biaya dan Penerapan Cost-Volume-Profit (CVP) pada UMKM Lemang Batok di Kota Tebing Tinggi - Rika Surianto Zalukhu; Rapat Piter Sony Hutauruk; Daniel Collyn; Metyria Imelda Hutabarat (Accounting Progress, 2025)
This study aims to analyze cost behavior in the Lemang Batok micro-enterprise (UMKM) in Tebing Tinggi City as a basis for more accurate production planning and pricing decisions. This research employs a descriptive qualitative approach using monthly production cost data obtained from the enterprise’s financial records. Total cost function was formulated to identify fixed costs, variable costs per unit, and the overall cost structure. A cost–volume–profit (CVP) analysis was then conducted to determine the break-even point and assess profit sensitivity to changes in production volume. The results indicate that the Lemang Batok enterprise carries fixed costs of IDR 3,100,000 per month and variable costs of IDR 415 per unit, resulting in a total cost function of Y = 3,100,000 + 415X. The CVP analysis indicates that the break-even point is reached at a production volume of 105 units per month at a selling price of IDR 30,000 per unit, while increasing production up to 700 units can significantly reduce the average unit cost and enhance the contribution margin. These findings demonstrate that separating mixed costs and applying CVP analysis provide a more accurate foundation for cost control and pricing decisions in micro-enterprises. This study contributes to the literature on cost behavior in traditional food-based micro-enterprises and offers practical recommendations for improving efficiency and profitability.